2010
DOI: 10.5012/bkcs.2010.31.02.415
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Effect on CO Oxidation over Highly Ordered Mesoporous Silver Catalyst

Abstract: Highly ordered mesoporous silver material was successfully synthesized from a mesoporous silica template (KIT-6) with 3-D channel structure using the nano-replication method. The effects of H2 or O2 pretreatments on the catalytic performance of the mesoporous silver were investigated using a temperature programmed CO oxidation technique in a fixed bed reactor. The mesoporous silver material that was pretreated with H2 exhibited an excellent catalytic activity compared to the as-prepared and O2-pretreated catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The mesoporous silica template (KIT-6) was synthesized following previously reported methods [26,[36][37][38][39][40]. A triblock copolymer (Pluronic P123, EO 20 PO 70 EO 20 , Aldrich) and tetraethylorthosilicate (TEOS, Aldrich) were utilized as the structure-directing agent and framework source, respectively.…”
Section: Catalyst Synthesismentioning
confidence: 99%
“…The mesoporous silica template (KIT-6) was synthesized following previously reported methods [26,[36][37][38][39][40]. A triblock copolymer (Pluronic P123, EO 20 PO 70 EO 20 , Aldrich) and tetraethylorthosilicate (TEOS, Aldrich) were utilized as the structure-directing agent and framework source, respectively.…”
Section: Catalyst Synthesismentioning
confidence: 99%
“…Electronic industry consumes large amounts of silver powder that is usually used as conductive paste [13][14][15][16]. Several studies have indicated that mesoporous silver powders with higher porosity and larger surface area engender higher application efficiencies such as reducing firing temperature of conductive film [17], enhancing the resistance of heat exchanger material at ultralow temperature [18], or increasing catalytic activity of an oxidation reaction [19,20]. Recently, due to the rapid development of electronic industry, it demands a huge amount of high quality silver powder.…”
Section: Introductionmentioning
confidence: 99%